Synthesis and Preliminary In Vitro Anti-inflammatory Evaluation of Mannich Bases Derivatives of 4’-Methoxy-substituted of Asymmetrical Cyclovalone Analogs - Rahmawati, Nur; Hariyanti, Hariyanti; Saputri, Fadlina Chany; Hayun, Hayun (Indonesian Journal of Pharmacy, 2020)
Two of Mannich bases derivatives of 4’-methoxy-substituted of asymmetrical cyclovalone analog (ACA) (2a and 2b) were synthesized. The synthesized compounds and the other two Mannich bases derivatives of 4'-methoxy-substituted ACA (2c and 2d) were evaluated for their in-vitro anti-inflammatory activity preliminary by protein denaturation inhibition method using a final concentration of 1.57 μM. The study found that all the Mannich bases exhibited anti-inflammatory potential with inhibition ranging from 33.17- 42.47%. The activity of 2b (42,47%) and 2d (41.90%) was higher than that of diclofenac sodium (35.27%) and the parent compound 1 (38.16%). As a conclusion,  2b and 2d have a prospect as a potential candidate for an anti-inflammatory agent. Further study should be done using more specific methods.